Práticas e avaliação da sustentabilidade nos canteiros de obras - Zeule, Ludimilla de Oliveira (2014)
This paper addresses the concept of sustainability and its application in construction sites. The construction sector seen as great usufruidor of natural resources and the waste generator to interfere in the natural characteristics of the environment. In order to change this paradigm is a set of necessary actions related to the integration of sustainable practices that seek to reduce waste indices, improve quality processes and qualify manpower. Seeking to identify how sustainable a construction site can be, this work proposes a methodology for evaluating the implementation of sustainability based on practices aimed at execution phase adopted by seals environmental certifications existing, through a checklist of six items: sustainable site, rational use of water, rational use of energy, materials and resources, environmental quality, and innovation processes. The main purpose of this tool is to identify good practices, scoring the situations observed and classify sites in sustainability levels. The checklist was applied in six construction systems sites and geographies distinct, aiming at studying the different occurrences. In a final step the results of the visits were compiled, and from exposure of the analyzed data it was found that the checklist should function as a guide of recommendations in the execution phase of construction. It was found a list of viability for different types of works, such as Housing Development Social Interest (EHIS), certified environmentally or not, located in different geographical regions. It was concluded that the companies visited are concerned with environmental issues in accordance with the business strategy adopted, and that sometimes occurs lack of planning, knowledge and support tools for adequate insertion of sustainable practices at construction sites.